Relation between Genomic DNA Breakpoints in MLL Gene and Treatment Outcome in Infants with Acute Leukemia - GA Tsaur; C Meyer; TO Riger; AM Kustanovich; EV Fleischman; YuV Ol’shanskaya; AM Popov; OI Sokova; EA Matveeva; OV Nikulina; AE Drui; OR Arakaev; et al. (Клиническая онкогематология)
Aim. To evaluate the relation between genomic DNA breakpoints in MLL and translocation partner genes (TPG) and clinical parameters of infant AL.